Assessment of the Prevalence and Anatomical Variations of the Retromolar Canal using Cone Beam Computed Tomography: A Cross-sectional Study: The Prevalence and Anatomical Variations of the Retromolar Canal using CBCT - Moshfeghi, Mahkameh; Ghazizadeh Ahsaie, Mitra; Jafarian Amiri, Maedeh; Mosaffa, Mehrnaz; Momeni, Amir Ahmad (Journal of Dental School, 2023)
Objectives The aim of this study was to evaluate the prevalence and anatomical variations of retromolar canal (RMC). Since RMC contains neurovascular bundle that contribute to the innervation and nutrition of the pulp and periodontium of the mandibular teeth, it is necessary to pay attention to the clinical importance of this landmark, to prevent possible surgical complications and anesthetic failures. Methods In this descriptive-analytical study, 450 CBCT scans were evaluated. The scans were evaluated for presence of the RMC and linear measurements (distance to second and third molar, height, width and diameter) were made with NNT software. Descriptive statistics were used to assess data. Data were analyzed using paired t-test adopting significance for p value ≤0.05. Results The prevalence of RMC was 7.1%. Among of the existed RMC, 71.9% were unilateral and 28.1% were bilateral. The mean height of canal was 9.33 ± 3.65 mm, and the mean width of the canal was 0.87 ± 0.4 mm. The mean distance of RMC to the third and second molar were 10.44 ± 5.1 mm and 11.71 ± 3.73 mm respectively. No significant differences were detected between the two genders. Conclusion The prevalence of the RMC was observed to be 7.1% and was well observed in CBCT images. Accurate assessment of this anatomic landmark helps prevent surgical complications especially prior to third molar anesthesia and extraction.